Turkish Adaptation Of The Nurse Manager Practice Environment Scale - Ayşe Tosun; Aytolan Yıldırım (Association of Nurse Managers, 2021)
INTRODUCTION: The research was carried out in order to adapt the 'Nurse Manager Practice Environment Scale ' to Turkish. METHODS: The research was carried out in a methodological design and the sample consisted of 243 participants who completed the questionaires completely among 273 manager nurses in five public, two university, and two private hospitals in Ankara. The data were collected by using a questionnaire containing 10 questions and 'Nurse Manager Practice Environment Scale'. The questionnaires that were fully completed were statistically evaluated and tested regarding language validity, content validity, confirmatory factor analysis, Cronbach's alpha coefficient, item total score correlation analysis, test-retest method and Pearson product moment correlation for validity and reliability. RESULTS: The Content Validity Index of the scale that language validity provided is.935. Cronbach α reliability coefficient of the scale is.96. Strongly positive correlations were detected between item total scores of.49 and.80. Test-retest consistency was at a high level as assessed by t test in dependent groups (t═1.019 p>.05) and also by Pearson correlation analysis (r =.97, p<.01). The eight-factor structure of the scale fit well to the confirmatory factor analysis. DISCUSSION AND CONCLUSION: 'Nurse Manager Practice Environment Scale' is a valid and reliable measurement tool for nurse managers in Turkish society. This scale can be used for evaluating the nurse manager practice environment in the field of health care.